Hyaluronic acid versus dexamethasone for the treatment of recurrent aphthous stomatitis in children: efficacy and safety analysis - Yang,Zheng (2020)
The objective of this study was to compare the safety and efficacy of 0.2% hyaluronic acid (HA) topical gel and dexamethasone topical ointment in the treatment of recurrent aphthous ulcers (RAU) in children. This retrospective observational study included 104 patients who had more than two episodes of oral aphthous ulcers per year and were treated with HA (n=52) or dexamethasone (n=52) from August 15, 2014 to September 3, 2018. Therapy efficacy was evaluated based on the ulcer size and pain score before versus 7 days after either therapy. The paired t-test, chi-squared test, and independent t-test were utilized for statistical analyses. There was no significant difference in ulcer size or pain score between the HA and dexamethasone groups, on day 1 or day 7. Both treatments were tolerated well and no side effects were reported. No significant differences in body temperature, respiration rate, pulse, or systolic/diastolic blood pressure were observed between the start (day 1) and end of treatment (day 7), for either treatment. HA and dexamethasone showed similar efficacy in reducing ulcer size and pain scores, and were tolerated equally well in children with RAU. Future high-quality studies with larger numbers of patients are needed to confirm our findings.